Macroscopic and histologic regression of duodenal polyposis with FOLFOX4 chemotherapy for an ileal pouch adenocarcinoma in a patient with familial adenomatous polyposis - Pioche, M.; Aguero Garcete, G.; Forestier, J.; Lépilliez, V.; Nozières, C.; Lombard-Bohas, C.; Saurin, J.-C. (Endoscopy, 2012)
Severe (stage IV) duodenal polyposis is difficult to manage in patients with familial adenomatous polyposis (FAP), with no effective medical treatment, complex endoscopic treatment modalities, and a high morbidity and mortality from pancreaticoduodenectomy. We present the case of a 44-year-old woman with FAP, stage IV duodenal polyposis, and with an ileal pouch adenocarcinoma that required surgery and adjuvant chemotherapy. Her duodenal polyposis regressed to stage II after four sessions of FOLFOX4 adjuvant chemotherapy, which avoided the need for aggressive endoscopic therapy or pancreatoduodenectomy in this patient.